A qualificação profissional na regulação da gestão da força de trabalho dos trabalhadores portuários avulsos (TPAs) do Porto de Paranaguá-PR - Silva, Luceli Gomes da (2019)
This dissertation investigates the professional qualification of the single dock worker (TPA), in the new regulation of the management of the single workforce in the port of Paranaguá-PR, after the implementation of the Law of Ports, the law n ° 8.630 of 1993, and its edition, the Law n ° 12.815 of 2013- both known as Port modernization laws. The modernization of the handling and packaging methods of ship loads and the introduction of logistic loading and unloading technologies, which increase the productivity and speed of port operations, has added a qualification differentiated from the TPAs, adjusted to the new demands of professional competencies and multifunctionality. In this context, the management of the single workforce has been executed by a non-profit institution, but maintained by the operators in the port, the OGMO (Labour Manager Organ), and this is the legal role of professionally qualifying the TPAs for the new functions of ports operations, which resulted in the change in qualification, which is now normalized through the certification of the courses offered by the OGMO, via an agreement with the navy through the Professional Marítime Education Program (PREPOM). Thus, the main objective is to provide a general framework of the qualification offered in the new regulation of the single workforce, considering the direct relations established between capital and work after employer control over the management of labour force, and above all the eligibility criteria for the TPA. Thus, we sought to investigate how the actors incorporated this new logic of professionalization, considering that currently the qualification certified by the PREPOM courses is a mandatory requirement for the TPA to remain in the labor market. Among the categories of the TPAs chosen for the object of analysis are the dockers, because they are the most numerous category in the port work, and the block, and the block, for currently constituting multifunctional workers. For the theoretical analysis of research, the concept of qualification for work as a social relationship was adopted, supported by George Friedmann and Pierre Naville. Among the methodological procedures, we used a bibliographical and documentary survey of primary sources, such as the norms governing PREPOM, and port legislation; of field research annotations; indirect observation; of semi-structured interviews with port workers. The research pointed out that the TPAs of the port of Paranaguá incorporated in their own discourses the need for qualification to face the modernization of port operations so that they can remain in the labor market. It is concluded that for the TPAs, the tacit knowledge becomes necessary, as they know the need to qualify to remain in the labor market, and know of the deficiency of PREPOM courses, insufficient to qualify them adequately, contradicting what is expected of your new professional profile.